Skrining Probiotik Asal Produk Komersil yang Berpotensi Sebagai Inhibitor a-Glukosidase - Angelin Christin; Edy Fachrial (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Various types of food products have good and bad effects on human health. One type of food that provides positive benefits is functional food. Functional foods are foods or beverages that are not only consumed to fulfill nutritional needs, but also provide good effects on the body's health and help reduce the risk of serious diseases. An example of functional food is probiotic drinks, which are known to support digestive health and strengthen the immune system. The content of probiotic drinks has a good impact on digestion and is able to inhibit α-glucosidase, so it is good to be consumed as a supplement for type 2 diabetes patients. The research focused on testing the potential of probiotics derived from commercial products on α-glucosidase enzyme activity. This type of research is laboratory experimental research with In Vitro method. The samples in this study are beverage samples with various types of brands containing probiotic milk that will be tested. The results showed that of the 8 probiotic isolates isolated from commercial products L-Bio, Yakult, Biokul and Max biotic have tolerance to acid and bile salt. Probiotic isolates in this study did not show antimicrobial activity. Screening of probiotics from commercial products with the most potential as α-glucosidase inhibitors was yakult.